Detailed test-particle simulations of energetic particles interacting with magnetized plasmas I. Two-component turbulence. Issue 8 (15th October 2020) - Arendt, V.; Shalchi, A.
Abstract: Energetic particles interacting with interplanetary or interstellar plasmas experience transport along and across large scale magnetic fields. In particular the diffusion of particles in the perpendicular direction is difficult to understand theoretically. However, significant progress has been achieved due to the development of test-particle simulations, non-linear systematic theories, and heuristic descriptions of the transport. Non-linear analytical theories often work well but in some cases they require to incorporate a correction factor a 2 in order to achieve perfect agreement with simulations. It was stated previously that a 2 ≈ 1 / 3 but there are also cases where a 2 ≈ 1 was found meaning that no correction factor is needed. It is the purpose of this paper to present comprehensive test-particle simulations for slab/2D turbulence also known as two-component turbulence. We consider a wide range of parameters and perform 48 different runs. In all cases we compare our numerical findings with analytical theories in order to determine the exact value of a 2 for each case. We also discuss the physical meaning of a 2 which should eventually lead to further improvements of analytical theories for perpendicular transport.